The Influence of Corporate Social and Governance Pillars on Green Innovation in Southeast Asian Energy Sector Public Companies - Amelia Putri; Tafdil Husni; Fajri Adrianto (Dinasti Review, 2025)
This research aims to analyze the relationship between Corporate Social and Governance pillars and green innovation in the Southeast Asian energy sector. It is a quantitative study that relies on secondary data from Refinitiv Eikon and relevant websites, analyzed using panel data regression with STATA 14 software. The research focuses on public companies in the Southeast Asian energy sector, using purposive sampling based on specific criteria, including operating between 2020-2023, having complete ESG data, and issuing financial statements during this period. This research provides a structured approach to understanding the impact of corporate social pillar includes workforce, human rights, community, and product responsibility, while the governance pillar comprises management, shareholders, and CSR strategies on green innovation in the Southeast Asian energy sector. The results of the study indicate a significant relationship between company performance and green innovation in the ASEAN energy sector. Analysis of sustainable performance variables, based on the ESG categories from the Refinitiv Eikon Database, reveals that social and governance-related scores influence green innovation in companies. Specifically, the workforce score, human rights score, and product responsibility score have a positive and significant relationship with the company’s green innovation, while the community score shows a negative and significant relationship. In terms of governance, the management score has a negative and significant relationship with green innovation, whereas the shareholder score is positively and significantly related to green innovation. The CSR strategy score, although positive, does not have a significant relationship with green innovation in the ASEAN energy sector. This study highlights the importance of social and governance factors in driving green innovation and the need to pay close attention to specific elements that can support the successful implementation of green innovation in this sector.